2015
DOI: 10.1177/1473871615575079
|View full text |Cite
|
Sign up to set email alerts
|

Visual analysis of online social media to open up the investigation of stance phenomena

Abstract: Online social media are a perfect text source for stance analysis. Stance in human communication is concerned with speaker attitudes, beliefs, feelings and opinions. Expressions of stance are associated with the speakers' view of what they are talking about and what is up for discussion and negotiation in the intersubjective exchange. Taking stance is thus crucial for the social construction of meaning. Increased knowledge of stance can be useful for many application fields such as business intelligence, secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…uVSAT by Kucher et al . [KSBK*16] provides a separate representation of individual documents based on selected subsets of aggregated emotion/stance value series initially presented to the user (see Figure (b)). Ruppert et al .…”
Section: Sentiment Visualization Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…uVSAT by Kucher et al . [KSBK*16] provides a separate representation of individual documents based on selected subsets of aggregated emotion/stance value series initially presented to the user (see Figure (b)). Ruppert et al .…”
Section: Sentiment Visualization Techniquesmentioning
confidence: 99%
“…Image courtesy of Florence Ying Wang . (b) uVSAT [KSBK*16] provides a detailed view of a selected document for the purposes of stance analysis. (c) IdeaFlow [WLC*16] uses sentiment analysis results for the lead‐lag analysis of ideas.…”
Section: Sentiment Visualization Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that sentiment features improve the stance classification results, which indicates that knowledge of the sentiment in a tweet facilitates the identification of stance. In their study, Kucher et al (2016b) described an approach for stance analysis based on sentiment or certainty considerations and presented the uVSAT tool for visual stance analysis, the analysis of temporal and textual data, and the exportation of stance markers in order to prepare a stance-oriented training data set.…”
Section: Computational Approaches To Stance Identificationmentioning
confidence: 99%